Public Relations Management in Enhancing the Collaboration Between SMK Negeri 6 Malang City and the Industrial Sector - Effendi, Muhammad Idris; Nurjanah, Lailatul (Universitas Ahmad Dahlan, 2025)
This study explores the role of the Public Relations (PR) division at SMK Negeri 6 Malang City in strengthening collaboration with the industrial sector to ensure that graduates possess competencies aligned with labor market demands. The primary issue addressed is how PR can bridge the gap between vocational education and industry requirements through strategic communication and partnership programs. The purpose of this research is to identify the strategies employed by the PR division in establishing and maintaining industrial partnerships, as well as to understand the challenges encountered. The study adopts a qualitative approach utilizing in-depth interviews, observations, and document analysis. The findings indicate that programs such as industrial classes and job fairs significantly contribute to enhancing students’ technical skills and soft skills required in the workplace. Despite facing resource limitations and differing expectations between institutions and industries, the established collaborations have had a positive impact providing students with valuable practical experiences and improving the school’s reputation in the broader community. In conclusion, the development of sustainable industrial partnerships is a crucial factor in increasing the relevance of vocational education and ensuring graduates' employability.